Health risk assessment of urban population exposure to contaminants in the soils of the Southern Kuzbass; Proceedings of SPIE; Vol. 9680 : Atmospheric and Ocean Optics: Atmospheric Physics - Osipova N. A. Nina Aleksandrovna; Tarasova N. P.; Osipov K. Yu.; Maximova D. I. (Atmospheric Physics And Climate, 2015)
Title screen